Shelf Life Extension of Chilled Pork by Optimal Ultrasonicated Ceylon Spinach (Basella alba) Extracts: Physicochemical and Microbial Properties - Yuthana Phimolsiripol; Srirana Buadoktoom; Pimporn Leelapornpisid; Kittisak Jantanasakulwong; Phisit Seesuriyachan; Thanongsak Chaiyaso; Noppol Leksawasdi; Pornchai Rachtanapun; Nareekan Chaiwong; Sarana Rose Sommano; Charles S. Brennan; Joe M. Regenstein (Foods, 2021)
The effect of ultrasonication on the antioxidant and antibacterial properties of Ceylon spinach (Basella alba) extracts (CE) and the shelf life of chilled pork with CE were studied. The CE were ultrasonicated at different power levels (60–100%) for 10–40 min in an ultrasonic bath with the rise of antioxidant activities (p ≤ 0.05) proportional to the ultrasonication time. The additional investigation of antibacterial activities showed that the ultrasonicated extracts (100 mg/mL) could inhibit and inactivate Staphylococcus aureus and Escherichia coli with the optimal condition of 80% power for 40 min. For shelf life testing, fresh pork treated with the ultrasonicated extracts at 100 and 120 mg/mL had lower values of thiobarbituric acid reactive substances (TBARS) than the control (without dipping). For food safety as measured by the total microbial count, the fresh pork dipped with 100–120 mg/mL CE extract could be kept at 0 °C for 7 days, 2 to 3 days longer than control meat at 0 and 4 °C, respectively. A sensory evaluation using a nine-point hedonic scale showed that fresh pork dipped with 100-mg/mL CE extracts was accepted by consumers. It is suggested that CE extracts can be applied in the food industry to enhance the quality and extend the shelf life of meat products.